Knowledge, attitude and practice of family planning among women of reproductive age group attending outpatient department in a tertiary centre of Northern India - Qazi, Mahvish; Saqib, Najmus; Gupta, Sachin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: India with 1.35 billion people is the second most populated country in the world next to China. Total fertility rate of India is 2.2 and the current total fertility rate of Jammu and Kashmir is 1.7 which is still lagging behind various states. This study was conducted to investigate the knowledge, attitude and practices of contraception in women of reproductive age in this set up. Methods: The present cross-sectional study was carried out in patients attending OPD (outpatient department) of Obstetrics and Gynecology at ASCOMS, Jammu, Jammu and Kashmir, India from 1st September 2017 to 31st August 2018. 200 married women aged between 18-49 years were included in this study. Socio-demographic characteristics of the women, their knowledge, attitude and practices on contraception were evaluated with the help of predesigned questionnaire. Results: Out of 200 women, maximum respondents belong to age group of 21-25 years (75.6%). Most of the contraceptive non-users belongs to age below 20 years (62.5%). Majority of respondents were Hindu (70.37%), maximum studied up to secondary level education (84.61%), 70.30% were housewives and 56.58% belongs to middle class. In 45% of respondents, media was the main source of information. Preferred spacing method was condom in 85% of cases. 68% women had knowledge of female sterilization. According to most women, family planning methods are meant for limitations of birth (43%) and 36% meant for spacing of birth. 80% women had positive attitude towards contraceptive usage. 50% experienced side effects with the use of contraceptives. The most common side effect was menstrual irregularities in 25% of cases. Most common reason for not using contraceptive methods among non-respondents were lack of knowledge in 50% of cases. Conclusions: The study showed that inspite of having good knowledge, utilization of contraceptives were less because of large family norm, religious myth, cultural and political barriers. Ignorance regarding use and side effects of various contraceptive methods is another reason for inadequate practice of family planning methods.